The Role of PBC in Accelerating the Green Consumption Trend - Maulana, Lucky Hikmat; Pasaribu, Popy Novita; Ridiarsih; Marlina, Asti; Suwondo, Nanang (Indonesian Journal of Social Research (IJSR), 2025)
Green consumption is now a phenomenon that is not only growing at the global and national levels, but is also beginning to enter urban communities such as the city of Bogor in Indonesia. In an effort to mitigate environmental problems, green consumption behavior offers a strategic and sustainable approach, which is expected to build collective awareness among the community of the importance of an environmentally friendly lifestyle.  The trend of green consumption behavior, driven by awareness of the importance of protecting the environment and self-efficacy to support its implementation, is hampered by several factors. The correlation between the two can be examined using the Theory of Planned Behavior, which explains the relationship between environmental awareness and self-efficacy, which is formed from consumer interactions through attitude, subjective norms, and perceived behavioral control. This study aims to investigate the role of perceived behavior control in helping to accelerate the trend of green consumption among consumers of environmentally friendly products in Bogor City. In this study, data were obtained through the distribution of questionnaires to respondents selected using purposive sampling. The number of variables observed in this study was 20 indicators, resulting in a sample size of 100.  Respondent demographics were divided into 6 profile categories such as gender; generation; education; occupation; monthly expenditure; and residential area in Bogor City. The data were analyzed using PLS-SEM and processed with SmartPLS 4 software. The main findings show that the relationship between self-efficacy and PBC has the most significant pathway. In addition, the role of PBC as a psychological factor has a substantial contribution in bridging self-efficacy and green consumption, making it a key factor in strengthening individual self-efficacy to adopt green consumption behavior.